Recuperación de oro por gravimetría del mineral proveniente del Distrito Minero Nambija-Condominio Norte. - Enríquez Vera, Yadira Marisol (2015)
Gravity concentration is one of the separation processes more economical and efficient method that exists for particles with a narrow size range. The present research work has studied the main parameters of gravity concentration equipment; specifically the shaking table and Knelson concentrator for gold recovery of material from North Condominium of Nambija; in order to get better performances. For this reason, it was done the material preparation, crushing, grinding, mineralogical studies, and tests were conducted separately with the best grain size for the processes. First, in the shaking table with 128.2; 170.6; and 185.5 mesh; and then, in the Knelson concentrator with 70.6; 185.5 and 207 mesh. Finally, it was done an essay in which processes were used in combination. The gotten recoveries were acceptable; in the shaking table it was obtained a recovery of 20.19% with a grade of 1.04 ppm; in the Knelson concentrator a recovery of 50.37%, with a grade of 5.31 ppm, and with the combination of both processes it was achieved a recovery of 63.42% with a grade of 11.02 ppm.